2015
DOI: 10.1039/c5ay00808e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of methionine enantiomers by HPLC on the cyclofructan chiral stationary phase

Abstract: The enantiomeric separation of methionine by high performance liquid chromatography on various cyclofructan type chiral stationary phases in the polar-organic separation mode was studied. The effects of the mobile phase composition and temperature on the enantioselectivity of the enantiomers were investigated. The enantioselective separation was attained on the isopropylcarbamate cyclofructan 6 chiral stationary phase with methanol/acetonitrile/acetic acid/triethylamine (75/25/0.3/ 0.2 v/v/v/v) as a mobile pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…An HPLC-based method was developed for the separation of methionine enantiomers applying CF-based CSPs in PO mode [ 47 ]. The optimized method using isopropyl carbamate CF-6 bonded onto 5 µm silica particles was validated and successfully applied for the quantitative determination of the enantiomers of methionine in a dietary supplement sample.…”
Section: Recent Applications Of Cyclofructan-based Cspsmentioning
confidence: 99%
“…An HPLC-based method was developed for the separation of methionine enantiomers applying CF-based CSPs in PO mode [ 47 ]. The optimized method using isopropyl carbamate CF-6 bonded onto 5 µm silica particles was validated and successfully applied for the quantitative determination of the enantiomers of methionine in a dietary supplement sample.…”
Section: Recent Applications Of Cyclofructan-based Cspsmentioning
confidence: 99%
“…Figure 5 depicts the structures of CF6-P, CF6-RN and CF7-DMP. Afterwards, the same group also carried out numerous comparison studies on the chiral recognition ability of cyclofructan-based CSPs (IP-CF6, RN-CF6 and DMP-CF7, as well as cyclodextrin-based CSPs) for the separation of a wide range of racemic compounds, including some unique and novel compounds such as tetrahydrobenzimidazoles, biaryl atropisomers, ruthenium(II) polypyridyl complexes, 2-naphthol atropisomers, α-aryl ketones, and spirobrassinin [53,[58][59][60][61][62][63][64][65][66][67][68]. The research results showed that most of the chiral analytes studied were well separated on these F I G U R E 5 The structures of the cyclofructan-based CSPs used for IP-CF6, RN-CF6 and DMP-CF7 chiral selectors, which have good complementary enantioseparation for some analytes.…”
Section: Cyclofructans Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%
“…Amino acid analysis has a significant value in pharmaceutical, biochemical and clinical research [1]. Methionine (2‐amino‐4‐(methylthio) butanoic acid) (Figure S1) is an essential sulfur‐containing amino acid in the human body that has potential in protein synthesis and transmethylation reaction [2].…”
Section: Introductionmentioning
confidence: 99%